Mutation and Work Environment Effect on Employee Performance with Compensation as Mediation Variable - Agung Danu Wibowo; Agus Sudigdo (LPPM STIE KRAKATAU, 2026)
This study aims to analyze the effect of job rotation and work environment on the performance of patrol vessel crew members at the Ministry of Marine Affairs and Fisheries, with compensation as a mediating factor. The population consisted of patrol vessel crew members across Indonesia, with a sample of 133 respondents. A quantitative approach using path analysis was employed to examine the direct and indirect effects of the variables. The results show that compensation can mediate the effect of the work environment on performance, but it does not mediate the effect of job rotation on performance. This study is limited to employees of the Directorate General of Marine and Fisheries Resources Surveillance (Ditjen PSDKP), which may restrict the generalizability of the findings to other public sector organizations with different contexts and work systems. Based on these findings, the Ministry of Marine Affairs and Fisheries can redesign its job rotation policy to focus on enhancing employees’ experience, skills, and competence. Policies regarding the work environment and compensation should be integrated to improve patrol vessel crew performance while ensuring their welfare and loyalty, considering the high risks and remote locations involved.